The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber: a second species of the genus with 11-segmented antennae - Kazantsev, Sergey V.; Perkovsky, Evgeny E. (Zootaxa, 2020)
A new species of soldier beetles of the subfamily Cantharinae, Cacomorphocerus meridionalis sp. nov., is described from Upper Eocene Rovno amber. It is the second time that a Cacomorphocerus species with 11-segmented antennae has been discovered. The status of the tribe Cacomorphocerini is discussed.